(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Medicinal plants such as Stevia rebaudiana and Moringa oleifera are considered as a perspective platform for nanoparticles (NPs) synthesis since their bioactive compounds both accelerate NPs synthesis efficiency and stabilize them afterward. Nanoparticles of transition metals can be applied as a possible antimicrobial option in various areas, including medicine, biotechnology, and agriculture. Both S. rebaudiana and M. oleifera possess notable medicinal, antioxidant, and anti-inflammatory properties. In this work, the antibacterial activities of silver nanoparticles (AgNPs) synthesized using hydroponically grown S. rebaudiana and M. oleifera are compared. AgNPs synthesized using M. oleifera are predominantly spherical, while those synthesized using S. rebaudiana exhibit an irregular shape. Biosynthesized AgNPs were tested against Escherichia coli BW25113, Enterococcus hirae ATCC9790, and Staphylococcus aureus MDC5233. Both AgNPs suppressed the number of colony-forming units (CFU). Both AgNPs used have shown a concentration-dependent inhibitory effect on the bacterial specific growth rate. At concentration of 25 μg/mL M. oleifera-mediated AgNPs the specific growth rate of E. hirae and S. aureus was reduced by 45% and 30%, respectively, whereas for S. rebaudiana-derived AgNPs the bacterial growth decreased by 60%. Gram-negative E. coli has demonstrated more susceptibility to AgNPs. Thus, S. rebaudiana and M. oleifera can be used as effective platform for NPs synthesis. S. rebaudiana-mediated AgNPs have shown more significant antimicrobial activity compared to M. oleifera-derived NPs. This may be attributed to differences in the phytocompounds involved in NP synthesis, as well as to variations in the shape and size of the synthesized nanoparticles.